2018
DOI: 10.1002/14651858.cd008980.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Factor Xa inhibitors versus vitamin K antagonists for preventing cerebral or systemic embolism in patients with atrial fibrillation

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 68 publications
0
21
0
1
Order By: Relevance
“…Since 2010, four direct oral anti-coagulants (DOACs; ie, apixaban, 7 dabigatran, 8 edoxaban, 9 and rivaroxaban 10 ) have been approved for use in patients with non-valvular atrial fibrillation. Cochrane reviews and meta-analyses 11,12 found that these DOACs have similar efficacy to VKAs in primary and secondary prevention of stroke but are associated with about half the frequency of intracranial haemorrhage. However, none of the randomised controlled trials comparing DOACs and VKAs included patients with recent ischaemic stroke associated with atrial fibrillation (within the first few weeks)—presumably because of concerns about the risk of haemorrhagic trans formation of the ischaemic brain tissue or of other intracranial haemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, four direct oral anti-coagulants (DOACs; ie, apixaban, 7 dabigatran, 8 edoxaban, 9 and rivaroxaban 10 ) have been approved for use in patients with non-valvular atrial fibrillation. Cochrane reviews and meta-analyses 11,12 found that these DOACs have similar efficacy to VKAs in primary and secondary prevention of stroke but are associated with about half the frequency of intracranial haemorrhage. However, none of the randomised controlled trials comparing DOACs and VKAs included patients with recent ischaemic stroke associated with atrial fibrillation (within the first few weeks)—presumably because of concerns about the risk of haemorrhagic trans formation of the ischaemic brain tissue or of other intracranial haemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Oral anticoagulants (OAC) are beneficial in the prevention of ischaemic stroke and systemic embolism in patients with atrial fibrillation. Vitamin K antagonists (VKA) were the only option for OAC therapy for many years, but since 2010, direct thrombin inhibitors [2] (dabigatran) and factor Xa inhibitors [3] (apixaban, edoxaban and rivaroxaban)—termed non-vitamin K antagonist oral anticoagulants (NOAC)—have emerged as an alternative option.…”
Section: Introductionmentioning
confidence: 99%
“…Ein aktueller Cochrane-Review bestätigt die Empfehlung der ESC-Leitlinie: Er bescheinigt den NOAK gegenüber VKA ein signifikant besseres Verhältnis in der Reduktion von Schlaganfällen, sonstigen thromboembolischen Ereignissen und Todesfällen gegenüber dem Auftreten von Blutungen, wie sie alle Gerinnungshemmer hervorrufen [43]. Alle NOAK zeigten in den randomisierten klinischen Prüfungenmit graduellen Unterschiedenbei nierengesunden Patienten mit nvVHF sowie bei Patienten mit einer nicht dialysepflichtigen Niereninsuffizienz ein vergleichbares Effektivitäts-und Sicherheitsprofil gegenüber VKA.…”
Section: Diskussionunclassified